х-возьмём как емкость 2канистры.
5*х- емкость 1канистры.
х+5х+7=55
6х+7=55
6х=55-7
6х=48
х=48: 6
х=8-емкость 2 канистры
5*8=40-емкость 1 канистры.
пусть x- ёмкость 2 канистры. тогда 5*x- ёмкость 1 канистры.
составляем уравнение
x+5x+7=55
6х= 55-76x=48
х=48: 6x=8 -ёмкость 2 канистры
5*x=5*8=40 -ёмкость 1 канистры.
х-возьмём как емкость 2канистры.
5*х- емкость 1канистры.
х+5х+7=55
6х+7=55
6х=55-7
6х=48
х=48: 6
х=8-емкость 2 канистры
5*8=40-емкость 1 канистры.
пусть x- ёмкость 2 канистры. тогда 5*x- ёмкость 1 канистры.
составляем уравнение
x+5x+7=55
6х= 55-76x=48
х=48: 6x=8 -ёмкость 2 канистры
5*x=5*8=40 -ёмкость 1 канистры.